A script file for mix design of structural lightweight concrete - Abdullahi M.; Al-Mattarneh H.M.A.; Mohammed B.S.; Sadiku S.; Mustapha K.N.; Norhisham S. (2023)
This paper presents a script file for mix design of structural lightweight concrete based on ACI 211.2-98. Mix design of concrete is very complicated, time-consuming and tedious task. It requires reading and understanding of tables and charts in the standards. Flow charts and algorithms were developed and eventually converted into MATLAB codes in a script file. The program has been tested and was found capable of giving material constituents for the first trial batch of sand-lightweight and all-lightweight concrete mixtures. The script file is fast, simple and efficient in determining the constituent materials of structural lightweight concrete. 2010, INSInet Publication.